Pelatihan Pijat Oksitosin bagi Pendamping Ibu Nifas - Sumiaty, Sumiaty; Muliani, Muliani; Lisnawati, Lisnawati (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2020)
Inadequate milk production in the first days after delivery is caused by a lack of stimulation of the hormone prolactin and the hormone oxytocin. Decreasing milk production is caused by decreased stimulation of hormones prolactin and oxytocin. Efforts that can be made to stimulate the increase of hormone prolactin and oxytocin, including initiating early breastfeeding, expressing breast milk, and doing oxytocin massage, are practical and efficient in increasing milk production. Data from the Public Health Office of Palu in 2017 and 2018 showed that the average of exclusive breastfeeding coverage in 11 sub-districts in Central Sulawesi Province is <50% and specifically Kota Palu exclusive breastfeeding coverage only 49.6% in 2017 and then dropped to 49, 3% in 2018. Oxytocin massage training has never been conducted at the Tawaeli Community Health Center, especially for postpartum mothers companions such as Posyandu Cadres, Husbands, or Families. The method used in community service activities was discussions, simulations, and demonstrations using leaflet and audiovisual media. The number of puerperal mothers who attended the training was 25 people. The results of training activities for postpartum mothers in the Kayumalue Ngapa village obtained that the results of knowledge analysis overall increased in the knowledge of 25 participants after attending the training, with an average increase of 13 points. The p-value<0,001 results meant that statistically, there was a significant effect on the increase of knowledge of postpartum mothers companion after attending oxytocin massage training. To sum up that there is a significant increase in knowledge between before and after training on oxytocin massage in stimulating milk production. It is recommended that health workers need to be consistent and continuous in giving training to the companion of the postpartum mother (husband, family or cadre) in order to be able to assist the process of changing behavior for the postpartum mother to provide exclusive breastfeeding and conduct care during the postpartum period.